Comparison Between Drug Regulation in EU and Brazil - Panková, Miroslava; Klosová, Anna, 1942-; Villaverde Castro, José; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
Purpose of this dissertation is to compare drug regulation between EU and Brazil and to estimate the potential effect of drug price regulation on total pharmaceutical sales. Pharmaceutical industry drives medical progress and it is neccessary to control the industry, in order to provide safe and quality medicines. Firstly, dissertation reviews economics of regulation, regulatory process and main theories of economic regulation. Then it describes the pharmaceutical industry, health and R&D expenditures and drug development. Then, with use of a regression model, is estimated the potential effect of regulation on pharmaceutical sales.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of globalisation and european integration [obor dipl. práce]